Trio-pharmacophore DNA-encoded chemical library for simultaneous selection of fragments and linkers - Meiying Cui; Dzung Nguyen; Michelle Patino Gaillez; Stephan Heiden; Weilin Lin; Michael Thompson; Francesco V. Reddavide; Qinchang Chen; Yixin Zhang (Nature Communications, 2023)
Dual-pharmacophore DNA-Encoded Libraries (DELs) can generate large libraries, but linker optimisation is challenging. Here, the authors report a trio-pharmacophore DEL (T-DEL) for both de novo fragment identification and linker optimization of known fragment pairs.